2020
DOI: 10.3389/fmolb.2020.569414
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Analysis of Coronavirus Disease 2019 (COVID-19) Receptor ACE2 in Malignant Tumors: Pan-Cancer Analysis

Abstract: Background: Coronavirus disease 2019 (COVID-19) was first detected in patients with pneumonia in December 2019 in China and it spread rapidly to the rest of the world becoming a global pandemic. Several observational studies have reported that cancer is a risk factor for COVID-19. On the other hand, ACE2, a receptor for the SARS-CoV-2 virus, was found to be aberrantly expressed in many tumors. However, the characterization of aberrant ACE2 expression in malignant tumors has not been elucidated. Here, we conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 56 publications
1
13
0
Order By: Relevance
“…Our analysis of 12,664 tumours of 119 different subtypes identified renal cell carcinomas derived from the proximal tubulus and colorectal adenocarcinomas as the most frequently ACE2-positive cancer types, followed by gastric adenocarcinoma, ductal and papilla Vaterii-derived pancreatic adenocarcinoma as well as cholangiocellular and hepatocellular carcinoma of the liver. This finding is in complete agreement with data from “The Cancer Genome Atlas” (TCGA) summarised in two recent publications [ 7 , 10 ]. Other tumour entities which were often ACE2-positive were too rare for being separately analysed within ICGC/TCGA studies, for example clear cell carcinomas of the ovary and the endometrium which resemble the commonly positive clear cell carcinomas of the kidney and mucinous carcinomas of the ovary which resemble the commonly positive colorectal adenocarcinomas.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our analysis of 12,664 tumours of 119 different subtypes identified renal cell carcinomas derived from the proximal tubulus and colorectal adenocarcinomas as the most frequently ACE2-positive cancer types, followed by gastric adenocarcinoma, ductal and papilla Vaterii-derived pancreatic adenocarcinoma as well as cholangiocellular and hepatocellular carcinoma of the liver. This finding is in complete agreement with data from “The Cancer Genome Atlas” (TCGA) summarised in two recent publications [ 7 , 10 ]. Other tumour entities which were often ACE2-positive were too rare for being separately analysed within ICGC/TCGA studies, for example clear cell carcinomas of the ovary and the endometrium which resemble the commonly positive clear cell carcinomas of the kidney and mucinous carcinomas of the ovary which resemble the commonly positive colorectal adenocarcinomas.…”
Section: Discussionsupporting
confidence: 92%
“…Previous analyses of normal tissues have identified ACE2 protein expression in at least one cell type of the kidney, testis, placenta, stomach, duodenum, small intestine, colon, rectum, gallbladder, liver, pancreas, thyroid gland, heart muscle, few cells in the respiratory epithelium, and endothelial cells of small vessels [ 5 ]. RNA-based analyses have also demonstrated that ACE2 expression occurs to a varying extent in miscellaneous cancer types [ 7 , 8 , 9 , 10 ], and upregulation of ACE2 has been linked to adverse cancer features in renal clear cell carcinoma, breast cancer, thyroid cancers and gallbladder carcinoma [ 11 , 12 , 13 , 14 ]. It has also been speculated that—in addition to a stressed immune system and poor general health status of cancer patients—presence of a large number of ACE2-expressing cancer cells might facilitate virus replication and contribute to the high COVID-19 mortality of cancer patients [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…ACE2 is expressed in lymphomas [52] and SARS-CoV-2 infection is associated with increased severity and mortality in lymphomas [53]. However, these SARS-CoV-2-induced remissions of cHL and FL are very isolated events [2,3] compared to global cHL and FL cases and the magnitude of the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-tumor immunotherapy is a treatment method to control and eliminate tumor cells by restarting and maintaining the tumor-immune cycle and restoring or even enhancing the normal anti-tumor immune response of the body ( 34 ). Both tumor immunotherapy and targeted therapy can target a specific protein, but immunotherapy can stimulate and enhance the immune capacity of the body through this target.…”
Section: Immunotherapymentioning
confidence: 99%